Chemical composition, antifungal and antioxidant activity of Pelargonium graveolens essential oil - Ana M. Dzamic, Marina D. Sokovic, Mihailo S. Ristic, Slavica M. Grujic, Ksenija S. Mileski, Petar D. Marin (Journal of Applied Pharmaceutical Science, 2014)
The present study describes the chemical composition, antifungal and antioxidant activity of Pelargonium graveolens essential oil. The essential oil profile was determined by GC and GC-MS. The main compounds were citronellol (24.54%), geraniol (15.33%), citronellyl formate (10.66%) and linalool (9.80%). Minimal inhibitory concentrations (MIC) and minimal fungicidal concentrations (MFC) were recorded using the microdilution and macrodilution methods. Commercial antimycotic bifonazol was used as a control. The concentration of 0.25-2.5 mg/ml showed fungicidal activity. The most resistant fungi were Mucor mucedo and Aspergillus species. The antioxidant activity of pure essential oil was evaluated by means of the 2,2-diphenyl-1-picrylhydrazil (DPPH) radical assay. The essential oil of P. graveolens was able to reduce DPPH radicals into the natural DPPH-H form, and this activity was dose-dependent. The oil exhibited antioxidant activity and reduced DPPH to 50% at EC50 value of 0.802 mg/ml of oil solution.
Keywords: Pelargonium graveolens, essential oil, microdilution method, macrodilution method, DPPH.